2005
DOI: 10.1002/rcm.2015
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of sulphoxides by atmospheric pressure ionisation mass spectrometry

Abstract: An observation that a series of proprietary compounds containing a methyl thiophenyl group all underwent metabolic S-oxidation, and that the product ion spectra of the resulting S-oxides showed methyl radical loss under low-energy atmospheric pressure ionisation tandem mass spectrometry (API-MS/MS) conditions, has led to an investigation of the fragmentation of commercially available sulphoxides. The phenyl methyl sulphoxides studied do lose methyl radicals under MS/MS conditions on triple quadrupole mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The characterisation of sulphoxides carried out by Wright et al . utilised this approach to help identify the most favourable site of protonation and then to help rationalise the experimentally observed fragmentation and the structures of the product ions 23. Holman et al .…”
mentioning
confidence: 99%
“…The characterisation of sulphoxides carried out by Wright et al . utilised this approach to help identify the most favourable site of protonation and then to help rationalise the experimentally observed fragmentation and the structures of the product ions 23. Holman et al .…”
mentioning
confidence: 99%
“…This could correspond to a loss of a methyl unit. Literature confirms that this fractionation pattern strongly indicates an oxygenation of the sulphur 16…”
Section: Resultsmentioning
confidence: 53%
“…These values are comparable to those used to assign the sulfoxide oxygen as the site of protonation in a previous study. 2 Hence, it can be concluded that the most energetically favourable site of protonation for 4-benzenesulfinyl-3-methylphenylamine is the sulfoxide oxygen. This finding suggests that the 17 m/z unit loss from protonated 4-benzenesulfinyl-3-methylphenylamine is more likely to be a hydroxyl radical than the alternative, a molecule of ammonia.…”
Section: Resultsmentioning
confidence: 99%
“…1 Previous studies have investigated the structural features which lead to specific product ions or losses being observed for different classes of compounds using electrospray ionisation tandem mass spectrometry (ESI-MS/MS). [1][2][3] This approach is of interest for pharmaceutical drug metabolite identification because the fragmentation behaviour may indicate the type of metabolic change that has occurred, e.g.…”
mentioning
confidence: 99%